The Investigation of Die Back Edge Cracking in Flip Chip Ceramic Ball Grid Array Package (FC-CBGA) - Kornain, Zainudin; Jalar, Azman; Rasid, Rozaidi (Journal of Science and Technology, 2010)
The cracking between die back edge and top fillet for Flip Chip Ceramic Ball Grid Array (FC-CBGA) package due to thermal cycling have been investigated in this study. Finite Element Analysis (FEA) model was used to analyze the effect of fillet geometry and material properties of underfill upon stresses along the die back edge. The thermo-mechanical properties of commercial underfill were obtained by using Thermal Mechanical Analyzer (TMA) and Dynamic Mechanical Analyzer (DMA) as the input for the simulation. Die stress distribution for different fillet height and width were generated to depict variation of stress due thermal loading and the variations of tensile stress were discussed for parameter optimization. The effect of different underfill material properties were discussed as well for thermal stress reliability improvement.